Feasibility of False Lashes from Areca Fibers (Areca Catechi L.) for Cosmetic - muthia aprillia; Vivi Efrianova (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2023)
False eyelashes from plant fibers are a new alternative to making false eyelashes because using false eyelashes from human hair is prohibited by Islam. In addition, false eyelashes from natural fibers also have other advantages such as being environmentally friendly, affordable, and biodegradable. One of the fiber-producing plants is the betel nut. This study aims to determine the feasibility of false eyelashes from betel nut fiber. This type of research is experimental. The type of research data is primary data sourced from observation, documentation, and questionnaires. This research uses a questionnaire/ questionnaire instrument. In the organoleptic and hedonic testing of false eyelashes, the required panelists are 15 people, namely 3 (three) from MUA, 2 (two) from the eyelash industry, 2 (two) from cosmetology and beauty lecturers, 8 (eight) students from makeup and beauty. The results of the research on betel nut fiber false eyelashes based on laboratory tests have a very smooth texture, namely 1.93 tex, strong attractiveness of 9.37 g/tex, and very high elasticity of 5.59. and based on the results of the organoleptic test, the average score of the flexible panelists was 85.3% in the tapering category, the lightness panel average score was 84% ​​in the light category, and the average neatness panel score was 86.67% in the neat category. For the hedonic test, the average score of the panelists was 92% in the very like category, for the aesthetic test, the average score for the panelists was 89.3% in the beautiful category. It is recommended as additional knowledge to students about the feasibility of false eyelashes from areca fibers for makeup.